Indian Publications on SARS-CoV-2: A bibliometric study of WHO COVID-19 database (2020)
Background & aims: Nowadays, the whole World is under threat of Coronavirus disease (COVID-19). The ongoing COVID-19 pandemic has resulted in many fatalities and forced scientific communities to foster their Research and Development (R&D) activities. As a result, there is an enormous growth of scholarly literature on the subject. We here in this study have assessed the Indian publications contributions on COVID-19. Methods: WHO is curating global scientific literature on coronavirus since it declared COVID-19 a global pandemic through Global Research Database on COVID-19. The present study analyzed Indian publications on SARS-CoV-2 as found in WHO COVID-19 database. The research data was restricted for the period of March 2, 2020 to May 12, 2020. Results: The study found that there is a considerable and constant growth of Indian publications on COVID-19 from mid-April. It is interesting to note that, the most prolific authors belong to either AIIMS or ICMR institutes. Delhi state contributed highest number of publications on COVID-19. The AIIMS, New Delhi was the most productive institution in terms of publications. The Indian Journal of Medical Research has emerged as the productive journal contributing highest number of the publications. In terms of research area, the majority of the publications were related to Epidemiology. Conclusions: The highly cited publications were of evidenced based studies. It is observed that the studies pertaining to virology, diagnosis and treatment, clinical features etc. have received highest citations than general studies on epidemiology or pandemic.